Impact of an advanced technique to characterize Toll- Like Receptors ( TLR2 and TLR4 ) in tuberculosis - كاظم عباس مهدي احسان عيدان السيمري (مجلة جامعة دمشق للعلوم الهندسية, 2022)
A controlled case study has been carried among pateints with Tuberculosis ,who attended the Consultation Center of Chest and Respiratory diseases of  Basrah province during 1st  September 2020 to 1st  June 2021. From total number of (176) patients with Tuberculosis (TB) were selected from Basrah province that are included in the present study. In flow cytometry results, the present study found that TLR2 was present on monocytes surface in percentage 32.08% and in control group was 14.8% , and TLR4 appeared in  3.4% among TB patients and in control group was 0.8%.